Pemikiran Politik Amien Rais:Strategi Politik Adiluhung Bagi Negara Demokrasi - Arif Muammar (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This article aims to analyze Amien Rais's political thinking. Using a qualitative approach with descriptive analysis, this study uses library data. The results of this study indicate that Amien Rais is a political figure who is strongly influenced by Islamic teachings in carrying out his political system. In his view, Islam cannot be used as the basis of a formal system in a country. But Islamic values must be carried out optimally in the system. This has led to a lack of appreciation of the values of other religions and values derived from the very rich local wisdom in Indonesia. In Amien Rais's thinking, a State must adhere to always putting Islam as a source of moral-ethics in setting its political foundation in the life of the nation and state. Amien Rais argues that tauhid is a moral-ethical foundation in developing a political system which is then formulated into the politik adiluhung.